2023
DOI: 10.1002/cjoc.202300494
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Triazine Framework Nanosheets: Synthesis and Energy Conversion and Storage

Zhao Liu,
Congxu Wang,
Wenjing Yuan
et al.

Abstract: Comprehensive SummaryCovalent triazine framework nanosheets (CTF NSs), an emerging class of two‐dimensional nanomaterials, have received great attention due to their abundant active sites, permanent porosity, molecular structural diversity, superior chemical/thermal stability, and short charge diffusion path, enabling technological breakthroughs in a myriad of applications. The forefront developments and applications of CTF NSs as photocatalysts and electrochemical electrodes have conferred superior performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 129 publications
(139 reference statements)
0
1
0
Order By: Relevance
“…46 Covalent triazine frameworks as facile and low-cost synthesized networks deliver a high reversible capacity due to their two-dimensional exfoliated few-layered structure. 47 A coating of carbon layer also regulates the superior sodium storage performances. 48 A recent investigation also showed that a carbon coating on the cathode and anode increases the conductivity of their materials and increases their performances.…”
Section: Effects Controlling the Sodium Storage Performancesmentioning
confidence: 99%
“…46 Covalent triazine frameworks as facile and low-cost synthesized networks deliver a high reversible capacity due to their two-dimensional exfoliated few-layered structure. 47 A coating of carbon layer also regulates the superior sodium storage performances. 48 A recent investigation also showed that a carbon coating on the cathode and anode increases the conductivity of their materials and increases their performances.…”
Section: Effects Controlling the Sodium Storage Performancesmentioning
confidence: 99%